Electronic Components
The electronic component addresses the issue of conductor protrusion and electrode cracking by employing a laminated structure with controlled dimensions and materials, ensuring robustness and reduced crack formation.
Patent Information
- Application Number
- JP2022059862
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-03-31
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-03-31
AI Technical Summary
The existing electronic components with increased cross-sectional area of internal conductors face the risk of protrusion from the laminate due to differing shrinkage rates, leading to cracks in external electrodes.
The electronic component design includes a laminated insulator section with band-shaped internal conductors, specific ratios of cross-sectional areas and lead-out portions, and a magnetic or non-magnetic layer to minimize protrusion and crack formation.
The design effectively reduces the likelihood of cracks in external electrodes by controlling the dimensions and materials of internal conductors within the insulator section, enhancing structural integrity.
Smart Images

Figure 0007605170000003 
Figure 0007605170000004 
Figure 0007605170000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to electronic components. [Background technology]
[0002] As an electronic component, an electronic component including a plurality of band-shaped internal conductors inside an element body is known (Patent Document 1). Patent Document 1 discloses an electronic component including a band-shaped internal conductor with a wide lead-out portion to an end face of a laminate in Fig. 2 and Fig. 5. It is said that this electronic component can prevent damage to a cutting blade or a dicer when cutting a mother laminate, can reduce the DC resistance value, and can prevent deformation of the laminate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-210204 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the electronic component of Patent Document 1, in order to increase the value of the current that flows, it is necessary to increase the cross-sectional area of the coil conductor. However, if the cross-sectional area of the internal conductor is increased, the internal conductor may protrude from the laminate due to the difference in shrinkage rate during firing between the insulating layer and the internal conductor, and the protrusion may cause cracks in the external electrode.
[0005] An object of the present disclosure is to provide an electronic component having a plurality of band-shaped internal conductors inside an element body, in which cracks are less likely to occur in the external electrodes. [Means for solving the problem]
[0006] The present disclosure includes the following aspects. [1] An insulating portion having a plurality of insulating layers laminated thereon; a plurality of band-shaped internal conductors embedded in the insulating portion; a first external electrode and a second external electrode provided to face an outer surface of the insulator and electrically connected to the internal conductor; Equipped with the insulator portion has upper and lower surfaces opposed to each other, first and second end surfaces opposed to each other, and first and second side surfaces opposed to each other, the internal conductor has a first main surface which is a main surface on the upper surface side and a second main surface which is a main surface on the lower surface side, The internal conductor is laminated via the insulating layer, the internal conductor has a line portion and a first lead portion and a second lead portion located on both ends of the line portion, the first lead portion is exposed at the first end surface, and the second lead portion is exposed at the second end surface, The total cross-sectional area of the line portions of the multiple internal conductors is 0.1 mm 2 Above 0.5mm 2 is as follows: a ratio of a distance between a first main surface of the line portion of the internal conductor closest to an upper surface of the insulator portion and a second main surface of the line portion of the internal conductor closest to a lower surface of the insulator portion to a height of the insulator portion is equal to or greater than 0.25 and is equal to or less than 0.55; The ratio of the width of the lead-out portion of the internal conductor to the width of the insulating portion is 0.40 or more and 1.0 or less. Electronic components. [2] The electronic component according to [1] above, wherein the number of the band-shaped internal conductors is 2 or more and 5 or less. [3] The electronic component according to [1] or [2] above, wherein the height of the insulating portion is 1.8 mm or more and 2.2 mm or less, and the width of the insulating portion is 2.3 mm or more and 2.7 mm or less. [4] The electronic component according to any one of the above [1] to [3], wherein the internal conductor has a protruding portion protruding from the first end face and the second end face. [5] The electronic component described in any one of [1] to [4] above, wherein a protruding distance of the most protruding internal conductor at the first end face and the second end face is 0.05 mm or less, and a ratio of the protruding distance of the most protruding internal conductor to a distance between a first main surface of the internal conductor closest to the top surface of the insulating portion and a second main surface of the internal conductor closest to the bottom surface of the insulating portion is 0.06 or less. [6] The electronic component described in any one of [1] to [5] above, wherein at the first end face and the second end face, a protruding distance of the internal conductor is 0.05 mm or less, and a ratio of the protruding distance of the internal conductor to a width of the internal conductor exposed from each end face is 0.06 or less. [7] The electronic component according to any one of the above [1] to [6], wherein the thickness of the insulating layer located between the internal conductors is 0.01 mm or more and 1.0 mm or less. [8] The insulating layer is Fe is 40 mol % or more and 49.5 mol % or less, calculated as Fe2O3; Zn is 2 mol % or more and 35 mol % or less, calculated as ZnO; Cu is 6 mol % or more and 13 mol % or less, calculated as CuO; Ni is 10 mol % or more and 45 mol % or less, calculated as NiO. The electronic component according to any one of the above [1] to [7], comprising a magnetic layer comprising [9] The electronic component according to any one of the above [1] to [8], wherein the insulating layer includes a non-magnetic layer.
[10] The nonmagnetic layer Fe is 40 mol % or more and 49.5 mol % or less, calculated as Fe2O3; Cu is 6 mol % or more and 13 mol % or less, calculated as CuO; Zn is 37.5 mol % or more and 54 mol % or less, calculated as ZnO The electronic component according to [9] above. Effect of the Invention
[0007] According to the present disclosure, it is possible to provide an electronic component in which cracks are less likely to occur in the external electrodes. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a perspective view illustrating a schematic configuration of an electronic component 1 according to a first embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view parallel to the LW plane of the electronic component 1 shown in FIG. [Diagram 3] FIG. 3 is a cross-sectional view parallel to the LT plane of the electronic component 1 shown in FIG. [Figure 4] FIG. 4 is a cross-sectional view parallel to the WT plane of the electronic component 1 shown in FIG. [Diagram 5] FIG. 5 is a partially enlarged view of the cross-sectional view shown in FIG. [Figure 6] FIG. 6 is a partially enlarged view of the cross-sectional view shown in FIG. [Figure 7] FIG. 7 is a cross-sectional view of an electronic component according to the second embodiment of the present disclosure. [Figure 8] FIG. 8 is a cross-sectional view of an electronic component according to another aspect of the second embodiment of the present disclosure. [Figure 9] FIG. 9 is a cross-sectional view of an electronic component according to a third embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an electronic component according to the present disclosure will be described in detail with reference to the drawings. However, the shape and arrangement of the electronic component and each component of the present embodiment are not limited to the examples shown in the drawings.
[0010] <Embodiment 1> A perspective view of an electronic component 1 of this embodiment is shown in Fig. 1, a cross-sectional view parallel to the LW plane in Fig. 2, a cross-sectional view parallel to the LT plane in Fig. 3, and a cross-sectional view parallel to the WT plane in Fig. 4. However, the shapes and arrangements of the electronic components and components of the following embodiments are not limited to the examples shown in the figures.
[0011] As shown in Figs. 1 to 4, the electronic component 1 of this embodiment is an electronic component having a substantially rectangular parallelepiped shape. The electronic component 1 generally includes an insulator section 7, a plurality of internal conductors 3 embedded in the insulator section 7, and a first external electrode 21 and a second external electrode 22 provided on both end surfaces of the insulator section 7. The insulator section 7 has a substantially rectangular parallelepiped shape. In the insulator section 7, two faces perpendicular to the L axis in Fig. 1 are referred to as a first end face and a second end face, respectively, faces perpendicular to the W axis are referred to as a first side face and a second side face, and faces perpendicular to the T axis are referred to as an upper face and a lower face, respectively. The internal conductor 3 includes a line portion 4, a first lead portion 5, and a second lead portion 6. The internal conductor 3 is electrically connected to the first external electrode 21 at the first lead portion 5, and is electrically connected to the second external electrode 22 at the second lead portion 6.
[0012] The electronic component of the present disclosure preferably has a length (L) of 2.5 mm or more and 4.0 mm or less, a width (W) of 2.0 mm or more and 3.0 mm or less, and a height (T) of 1.5 mm or more and 2.5 mm or less, and more preferably has a length of 2.8 mm or more and 3.5 mm or less, a width of 2.3 mm or more and 2.7 mm or less, and a height of 1.8 mm or more and 2.2 mm or less.
[0013] (insulation part) In the electronic component 1 of this embodiment, the insulator section 7 is configured by stacking a plurality of insulating layers. The insulating layers are stacked in the T direction in FIG.
[0014] The insulating layer includes a magnetic layer.
[0015] The magnetic layer contains at least Fe, Zn, Cu, and Ni.
[0016] The magnetic layer is made of a sintered magnetic material containing at least Fe, Zn, Cu, and Ni as main components.
[0017] The main components refer to components that make up the majority of the total components contained in the magnetic layer, and typically account for more than 50 mass % in total of the total components contained in the magnetic layer.
[0018] In the sintered magnetic material, the Fe content, calculated as Fe2O3, is preferably 40.0 mol % or more and 49.5 mol % or less (based on the total of the main components, the same applies below), and more preferably 45.0 mol % or more and 49.5 mol % or less.
[0019] In the sintered magnetic material, the Zn content, calculated as ZnO, is preferably 2.0 mol % or more and 35.0 mol % or less (based on the total of the main components, the same applies below), and more preferably 5.0 mol % or more and 30.0 mol % or less.
[0020] In the sintered magnetic material, the Cu content, calculated as CuO, is preferably 6.0 mol % or more and 13.0 mol % or less (based on the total of the main components, the same applies below), and more preferably 7.0 mol % or more and 10.0 mol % or less.
[0021] In the above sintered magnetic material, the Ni content is not particularly limited and may be the balance of the other main components Fe, Zn and Cu described above, and is preferably 10.0 mol % or more and 45.0 mol % or less (based on the total of the main components, the same applies below) and more preferably 15.0 mol % or more and 40.0 mol % or less, calculated as NiO.
[0022] By setting the contents of Fe, Zn, Cu, and Ni in the magnetic layer within the above ranges, excellent electrical properties can be obtained.
[0023] In the present disclosure, the sintered magnetic material may further contain an additive component. Examples of the additive components in the sintered magnetic material include, but are not limited to, Mn, Co, Sn, Bi, and Si. The contents (addition amounts) of Mn, Co, Sn, Bi, and Si are preferably 0.1 parts by mass or more and 1 part by mass or less in terms of Mn3O4, Co3O4, SnO2, Bi2O3, and SiO2, respectively, per 100 parts by mass of the total of the main components (Fe (in terms of Fe2O3), Zn (in terms of ZnO), Cu (in terms of CuO), and Ni (in terms of NiO)). The sintered magnetic material may further contain impurities that are unavoidable in the manufacturing process.
[0024] The distance between the upper surface 14 and the lower surface 13 of the insulating portion 7, that is, the height h1 of the insulating portion 7, is preferably 1.8 mm or more and 2.2 mm or less.
[0025] The distance between the first side surface 15 and the second side surface 16 of the insulator portion 7, ie, the width w1 of the insulator portion 7, is preferably not less than 2.3 mm and not more than 2.7 mm.
[0026] In one embodiment, the height h1 of the insulating portion 7 is not less than 1.8 mm and not more than 2.2 mm, and the width w1 of the insulating portion 7 is not less than 2.3 mm and not more than 2.7 mm.
[0027] The size of the insulator 7 is not particularly limited, but preferably, the height h1 of the insulator 7 is 1.8 mm or more and 2.2 mm or less, and the width w1 of the insulator 7 is 2.3 mm or more and 2.7 mm or less.
[0028] (inner conductor) A plurality of strip-shaped internal conductors 3 are embedded in the insulating portion 7. The term "strip-shaped" refers to a planar shape having a length and a width.
[0029] The internal conductor 3 may have a length in the L-axis direction, a width in the W-axis direction, and a thickness in the T-axis direction, and these axes may be linear. The internal conductor 3 has a first main surface 17 that is a main surface on the upper surface 14 side, and a second main surface 18 that is a main surface on the lower surface 13 side.
[0030] The internal conductor 3 has a line portion 4 and a first lead portion 5 and a second lead portion 6 located on both ends of the line portion 4. The first lead portion 5 is exposed at a first end face 11 and is electrically connected to a first external electrode 21. The second lead portion 6 is exposed at a second end face 12 and is electrically connected to a second external electrode 22.
[0031] There are multiple internal conductors 3, which are stacked with insulating layers interposed between them. With this structure, the electronic component of the present disclosure exhibits a coil-like function. The stacked internal conductors are arranged at substantially the same position when viewed from above. Note that substantially the same position includes not only a perfect match, but also a state in which most of the internal conductors overlap, for example, 90% or more of the area when viewed from above.
[0032] The number of the internal conductors 3 is preferably 2 or more and 5 or less, more preferably 3 or more and 5 or less, and further preferably 4 or 5.
[0033] The total cross-sectional area of the line portion 4 of the inner conductor 3 is preferably less than 0.1 mm 2 More than 0.5mm 2 The total cross-sectional area of the line portion 4 is 0.1 mm 2 By setting the total cross-sectional area of the line portion 4 to 0.5 mm or more, the resistance value of the internal conductor can be reduced. 2 By setting it as follows, the electronic component 1 can be made smaller.
[0034] The thickness t1 of the line portion 4 of the internal conductor 3 is preferably 0.03 mm or more, more preferably 0.04 mm or more. The thickness t1 of the line portion 4 of the internal conductor 3 is preferably 0.1 mm or less, more preferably 0.09 mm or less, and even more preferably 0.08 mm or less. In one embodiment, the thickness t1 of the line portion 4 of the internal conductor 3 may be preferably 0.03 mm or more and 0.1 mm or less, more preferably 0.04 mm or more and 0.08 mm or less.
[0035] The distance t2 between the line portions 4 of the internal conductor 3 (in other words, the thickness of the insulating layer between the line portions 4 of the internal conductor 3) is preferably 0.07 mm or more and 1.0 mm or less, more preferably 0.07 mm or more and 0.48 mm or less, and even more preferably 0.07 mm or more and 0.24 mm or less. By setting the distance t2 between the line portions to 0.07 mm or more, the insulation between the internal conductor layers can be more reliably ensured. Furthermore, by setting the distance t2 between the line portions to 1.0 mm or less, better electrical characteristics can be obtained.
[0036] The width w4 of the line portion 4 of the internal conductor 3 is preferably 0.3 mm or more and 2.0 mm or less, more preferably 0.5 mm or more and 1.5 mm or less, and further preferably 0.6 mm or more and 1.3 mm or less.
[0037] The width w3 of the lead-out portion of the internal conductor 3 is preferably 0.5 mm or more and 2.5 mm or less, more preferably 0.8 mm or more and 2.5 mm or less, and further preferably 1.0 mm or more and 2.0 mm or less.
[0038] The ratio (h3 / h1) of the distance h3 between the first main surface 17 of the line portion 4 of the internal conductor 3d closest to the upper surface 14 of the insulator 7 and the second main surface 18 of the line portion 4 of the internal conductor 3a closest to the lower surface 13 of the insulator 7 to the height h1 of the insulator 7 is preferably 0.25 to 0.55, more preferably 0.30 to 0.45. By setting h3 / h1 in the above range, it is possible to suppress the occurrence of cracks in the insulator and the external electrode.
[0039] The ratio (w3 / w1) of the width w3 of the drawn-out portion of the internal conductor 3 to the width w1 of the insulating portion 7 is preferably 0.40 or more and 1.0 or less, more preferably 0.40 or more and less than 1.0, and further preferably 0.50 or more and 0.8 or less.
[0040] Here, w3 is the width at approximately the center of the drawn-out portion in the axial direction of the internal conductor (i.e., the L-axis direction). w3 is the width of the internal conductor located at the center in the stacking direction among the internal conductors. For example, when there are five internal conductors, w3 is the width of the third internal conductor from the top surface 14 or the bottom surface 13. When there is an even number of internal conductors, w3 is the average of the widths of the two central internal conductors, in the illustrated example, internal conductors 3b and 3c.
[0041] By setting w3 / w1 in the above range, it is possible to suppress the occurrence of cracks in the insulating portion and the external electrode.
[0042] Let t1 be the thickness of the line portion 4 of the internal conductor, w4 be the width, and t2 be the distance between the internal conductors. Let t1 / w4 be x and t2 / t1 be y. (i) When the number of said internal conductors is three (x,y) is in the region bounded by A(0.051,1.0), B(0.051,5.9), C(0.2,5.9), D(0.2,4.4), and E(0.1,1.4). (ii) When the number of the inner conductors is four (x,y) is in the region bounded by F(0.038,0.26), G(0.038,5.2), H(0.2,5.2), I(0.2,4.9), and J(0.1,1.9). (iii) When the number of the inner conductors is 5 (x,y) is in the region bounded by K(0.031,0.53), L(0.031,4.9), M(0.15,4.9), and N(0.15,4.1).
[0043] By setting x and y to values within the above range, it is possible to suppress the occurrence of cracks and to increase the strength of the electronic component.
[0044] The inner conductor 3 has protruding portions protruding from the first end face 11 and the second end face 12 .
[0045] At the first end face 11 and the second end face 12, the protruding distances p1 and p2 of the most protruding internal conductor 3 are preferably 0.10 mm or less, more preferably 0.05 mm or less, and further preferably 0.04 mm or less. The lower limits of the protruding distances p1 and p2 are not particularly limited, but are preferably smaller, for example, 0.03 mm or more, or 0.01 mm or more.
[0046] In the first end face 11 and the second end face 12, the ratio (p1 / h2) of the protruding distance p1 of the most protruding internal conductor to the distance h2 between the first main surface 17 of the internal conductor 3d closest to the upper surface 14 of the insulator portion 7 and the second main surface 18 of the internal conductor 3a closest to the lower surface 13 of the insulator portion 7 is preferably 0.06 or less, more preferably 0.05 or less, and further preferably 0.04 or less. Moreover, p1 / h2 is, for example, 0.01 or more.
[0047] At the first end face 11 and the second end face 12, the ratio (p2 / w2) of the protruding distance p2 of the internal conductor 3 to the width w2 of the internal conductor 3 exposed from each end face is preferably 0.06 or less, more preferably 0.05 or less, and even more preferably 0.04 or less. Moreover, p2 / w2 is, for example, 0.01 or more. Here, w2 and p2 of the above-mentioned internal conductor are the width and protruding distance of the internal conductor located at the center in the stacking direction among the internal conductors. For example, when there are five internal conductors, w2 and p2 are the width and protruding distance of the third internal conductor from the upper surface 14 or the lower surface 13. Moreover, when the number of internal conductors is even, w2 and p2 are the average widths of the two central internal conductors, in the illustrated example, the two internal conductors 3b and 3c.
[0048] The conductive material constituting the internal conductor 3 is not particularly limited, and examples thereof include Au, Ag, Cu, Pd, Ni, etc. The material constituting the internal conductor 3 is preferably Ag or Cu, more preferably Ag. The conductive material may be one type or two or more types.
[0049] (external electrode) The external electrodes 21 and 22 are provided so as to cover the first end face 11 and the second end face 12 of the insulator portion 7 .
[0050] The conductive material constituting the external electrodes 21, 22 is not particularly limited, but may be, for example, one or more metal materials selected from Au, Ag, Pd, Ni, Sn, and Cu.
[0051] The external electrodes 21, 22 may be a single layer or a multilayer. In one embodiment, the external electrodes 21, 22 may be a multilayer, preferably two to four layers, for example, three layers.
[0052] In one embodiment, the external electrodes 21, 22 are multi-layered and may include a layer containing Ag or Pd, a layer containing Ni, or a layer containing Sn. In a preferred embodiment, the external electrodes 21, 22 are made of a layer containing Ag or Pd, a layer containing Ni, and a layer containing Sn. Preferably, the above layers are provided in the following order from the internal conductor side: a layer containing Ag or Pd, preferably Ag, a layer containing Ni, and a layer containing Sn. Preferably, the layer containing Ag or Pd is a layer formed by baking an Ag paste or a Pd paste, and the layer containing Ni and the layer containing Sn may be plated layers.
[0053] (Measurement method)
[0054] The height h1 and width w1 of the insulator portion 7, the cross-sectional area, thickness t1 and width w4 of the line portion 4 of the internal conductor 3, the distance t2 between the line portions 4, and the distance h3 between the first main surface 17 of the internal conductor 3d closest to the top surface 14 of the insulator portion 7 and the second main surface 18 of the internal conductor 3a closest to the bottom surface 13 can be measured as follows. The electronic component sample is hardened with resin so that the WT surface is exposed, and is polished in the L direction with a polisher until approximately the center of the insulator portion 7 is exposed. After polishing, the cross section is photographed with a digital microscope. The obtained image is analyzed using image analysis software to obtain the cross-sectional area, thickness t1, width w4, distance t2, and distance h3 of the internal conductor 3. Note that height h1 is the height at approximately the center in the width direction. Width w1 is the width at approximately the center in the height direction. Thicknesses t1 and t2 are the thicknesses at the center in the width direction of the internal conductor in the above cross section.
[0055] The width w3 of the lead-out portion of the internal conductor 3 can be measured as follows. The electronic component sample is hardened with resin so that the WT surface is exposed, and is polished in the L direction with a polishing machine until the approximate center of the lead-out portion in the L axis direction is exposed. After polishing, the cross section is photographed with a digital microscope. The obtained image is analyzed using image analysis software to obtain the width w3 of the lead-out portion of the internal conductor 3.
[0056] The above distance h2 and protruding distance p1 can be measured as follows. The electronic component sample is hardened with resin so that the LT surface is exposed, and polished in the W direction with a polishing machine until the approximate center of the internal conductor is exposed. After polishing, the cross section is photographed with a digital microscope. The obtained image is analyzed using image analysis software to obtain h1 and p1. Note that p1 is the distance from the tip of the most protruding internal conductor to a straight line connecting the contact point x1 between the insulator part 7 and the first main surface 17 of the internal conductor 3d closest to the upper surface 14 of the insulator part 7 and the contact point x2 between the insulator part 7 and the second main surface 18 of the internal conductor 3a closest to the lower surface 13 of the insulator part 7 in the obtained cross section.
[0057] The width w2 and the protruding distance p2 can be measured as follows. The electronic component sample is hardened with resin so that the LW surface is exposed, and polished with a polisher until the approximate center in the thickness direction of the internal conductor (in the illustrated example, the internal conductor 3b or 3c) located in the center in the T direction is exposed. After polishing, the cross section is photographed with a digital microscope. The obtained image is analyzed using image analysis software to obtain w2 and p2. Note that p2 is the distance from the tip of the internal conductor to a straight line connecting the first end face or second end face of the insulator part 7 and the contact points x3 and x4 with the internal conductor 3 in the obtained cross section.
[0058] (Manufacturing method) A method for manufacturing the electronic component 1 will now be described.
[0059] (1) Preparation of magnetic material (calcined magnetic powder)
[0060] First, a raw material of the magnetic material is prepared. The raw material of the magnetic material contains Fe, Zn, Cu, and Ni as main components. Usually, the main components of the raw material are substantially composed of oxides of Fe, Zn, Cu, and Ni (ideally, Fe2O3, ZnO, CuO, and NiO).
[0061] As the raw materials, Fe2O3, ZnO, CuO, NiO, and optional additive components are weighed to obtain a predetermined composition, mixed, and pulverized. The obtained powder is dried and calcined to obtain a calcined magnetic powder. Preferably, the obtained calcined magnetic powder is pulverized to obtain fine powder.
[0062] In the calcined magnetic powder, the Fe content, calculated as Fe2O3, is preferably 40.0 mol % or more and 49.5 mol % or less (based on the total of the main components, the same applies below), and more preferably 45.0 mol % or more and 49.5 mol % or less.
[0063] In the calcined magnetic powder, the Zn content, calculated as ZnO, is preferably 2.0 mol % or more and 35.0 mol % or less (based on the total of the main components, the same applies below), and more preferably 5.0 mol % or more and 30.0 mol % or less.
[0064] In the calcined magnetic powder, the Cu content, calculated as CuO, is preferably 6.0 mol % or more and 13.0 mol % or less (based on the total of the main components, the same applies below), and more preferably 7.0 mol % or more and 10.0 mol % or less.
[0065] In the above calcined magnetic powder, the Ni content is not particularly limited and can be the balance of the other main components Fe, Zn and Cu described above, and is preferably 10.0 mol % or more and 45.0 mol % or less (based on the total of the main components, the same applies below) calculated as NiO, and more preferably 15.0 mol % or more and 40.0 mol % or less.
[0066] In the present disclosure, the calcined magnetic powder may further contain additive components. Examples of additive components in the calcined magnetic powder include, but are not limited to, Mn, Co, Sn, Bi, and Si. The contents (addition amounts) of Mn, Co, Sn, Bi, and Si are preferably 0.1 parts by mass or more and 1 part by mass or less in terms of Mn3O4, Co3O4, SnO2, Bi2O3, and SiO2, respectively, per 100 parts by mass of the total of the main components (Fe (Fe2O3 equivalent), Zn (ZnO equivalent), Cu (CuO equivalent), and Ni (NiO equivalent)). The calcined magnetic powder may further contain impurities that are unavoidable in the manufacturing process.
[0067] In addition, it is safe to assume that the Fe content (converted into Fe2O3), Zn content (converted into ZnO), Cu content (converted into CuO), and Ni content (converted into NiO) in the above-mentioned calcined magnetic powder are substantially no different from the Fe content (converted into Fe2O3), Zn content (converted into ZnO), Cu content (converted into CuO), and Ni content (converted into NiO) in the above-mentioned sintered magnetic material after sintering.
[0068] (2) Preparation of conductive paste A conductive material is prepared. Examples of the conductive material include Au, Ag, Cu, Pd, and Ni, and preferably Ag or Cu, and more preferably Ag. A predetermined amount of conductive material powder is weighed out, and mixed with a predetermined amount of a solvent (e.g., eugenol), a resin (e.g., ethyl cellulose), and a dispersant in a planetary mixer or the like, and then dispersed in a three-roll mill or the like to prepare a conductive paste.
[0069] (3) Sheet production The magnetic materials prepared above are mixed to a predetermined ratio. The mixture is placed in a ball mill together with, for example, PSZ media, and an organic binder such as polyvinyl butyral, an organic solvent such as ethanol or toluene, and a plasticizer are added and mixed to obtain a slurry. Next, the slurry is formed into a sheet by a doctor blade method or the like, and the sheet is punched into a rectangular shape to produce a green sheet.
[0070] The thickness of the green sheet can be, for example, 20 μm to 100 μm, preferably 30 μm to 80 μm, more preferably 30 μm to 60 μm. By setting the thickness of the green sheet within the above range, high insulation properties and excellent electrical properties can be obtained.
[0071] Next, the conductive paste prepared above is screen-printed on the green sheet produced above to form a pattern of internal conductors.
[0072] (4) Lamination, bonding and singulation The green sheets obtained above are stacked in a predetermined order and thermocompression-bonded to produce a laminated block, which is then cut into individual pieces using a dicer or the like to obtain unfired bodies.
[0073] (5) Firing The green body obtained above is fired to obtain an electronic component body.
[0074] The firing temperature may be preferably 850°C or higher and 950°C or lower, and more preferably 900°C or higher and 920°C or lower.
[0075] The firing time may be preferably from 1 hour to 6 hours, more preferably from 2 hours to 4 hours.
[0076] After firing, the obtained element may be placed in a rotary barrel machine together with media and rotated to form R's on the edges and corners of the element.
[0077] (6) Electrode formation Forming the base electrode The base electrode can be formed by applying a conductive paste containing, for example, Ag and glass to the end surface from which the internal conductor is drawn out, and then baking it.
[0078] The thickness of the base electrode can be, for example, 5 μm or more and 80 μm or less, preferably 10 μm or more and 70 μm or less, and more preferably 40 μm or more and 60 μm or less.
[0079] The baking temperature may be, for example, 800° C. or higher and 820° C. or lower.
[0080] A metal layer coating is formed on the base electrode formed above by electrolytic plating. The coating may be a single layer or a multilayer. For example, a Ni coating may be formed on the base electrode, and then a Sn coating may be formed.
[0081] In the manner described above, the electronic component 1 of the present disclosure can be manufactured.
[0082] (Embodiment 2)
[0083] A cross section of the electronic component of the second embodiment is shown in Fig. 7. The cross section of Fig. 7 corresponds to the cross section of Fig. 4 of the first embodiment.
[0084] 7, the electronic component of the present embodiment 2 includes non-magnetic layers 31 and 32 in the insulating part 7. The other configuration is similar to that of the electronic component 1 of the above-mentioned embodiment 1. The electronic component of the present embodiment has excellent DC bias characteristics due to the inclusion of the non-magnetic layers.
[0085] The non-magnetic layer 31 is disposed between the internal conductors 3d and 3c so as to be in contact with the internal conductor 3d. Similarly, the non-magnetic layer 32 is disposed between the internal conductors 3b and 3a so as to be in contact with the internal conductor 3b.
[0086] The position of the non-magnetic layer is not limited to the above. For example, in one embodiment, the non-magnetic layer may be disposed between the internal conductors 3d and 3c and between the internal conductors 3b and 3a, as shown in FIG. 8, so as to be spaced apart from the internal conductors.
[0087] In another embodiment, the non-magnetic layer may be disposed only in the center portion in the lamination direction of the internal conductors, that is, between the internal conductors 3c and 3b.
[0088] In another embodiment, a non-magnetic layer may be disposed between all of the internal conductors.
[0089] The non-magnetic layer contains at least Fe, Cu, and Zn.
[0090] The non-magnetic layer is preferably made of a sintered non-magnetic material containing at least Fe, Cu, and Zn as main components.
[0091] In the sintered nonmagnetic material, the Fe content, calculated as Fe2O3, is preferably 40.0 mol % or more and 49.5 mol % or less (based on the total of the main components, the same applies below), and more preferably 45.0 mol % or more and 49.5 mol % or less.
[0092] In the sintered nonmagnetic material, the Cu content, calculated as CuO, is preferably 6.0 mol % or more and 13.0 mol % or less (based on the total of the main components, the same applies below), and more preferably 7.0 mol % or more and 10.0 mol % or less.
[0093] In the above sintered nonmagnetic material, the Zn content is not particularly limited and may be the balance of the other main components Fe and Cu described above, and may be preferably 37.5 mol % or more and 54 mol % or less (based on the total of the main components, the same applies below) and more preferably 40.5 mol % or more and 48 mol % or less, calculated as ZnO.
[0094] By setting the contents of Fe, Cu, and Zn within the above ranges, excellent electrical properties can be obtained.
[0095] In the present disclosure, the sintered non-magnetic material may further contain an additive component. Examples of the additive components in the sintered non-magnetic material include, but are not limited to, Mn, Co, Sn, Bi, and Si. The contents (addition amounts) of Mn, Co, Sn, Bi, and Si are preferably 0.1 parts by mass or more and 1 part by mass or less in terms of Mn3O4, Co3O4, SnO2, Bi2O3, and SiO2, respectively, per 100 parts by mass of the total of the main components (Fe (in terms of Fe2O3), Zn (in terms of ZnO), Cu (in terms of CuO), and Ni (in terms of NiO)). The sintered non-magnetic material may further contain impurities that are unavoidable in the manufacturing process.
[0096] The thickness of the nonmagnetic layers 31 and 32 is preferably 0.01 mm or more and 0.4 mm or less, more preferably 0.03 mm or more and 0.30 mm or less, and further preferably 0.06 mm or more and 0.20 mm or less.
[0097] The method for manufacturing the electronic component of this embodiment is similar to the method for manufacturing the electronic component 1 of the above-mentioned embodiment 1, except that it includes the step of providing a non-magnetic layer.
[0098] The raw material of the non-magnetic material contains Fe, Cu, and Zn as main components, and usually consists essentially of oxides of Fe, Cu, and Zn (ideally, Fe2O3, CuO, and ZnO).
[0099] As the raw materials, Fe2O3, CuO, ZnO, and, if necessary, additive components are weighed to obtain a predetermined composition, mixed, and pulverized. The obtained powder is dried and calcined to obtain a calcined nonmagnetic powder. Preferably, the obtained calcined nonmagnetic powder is pulverized to obtain a fine powder.
[0100] In the calcined nonmagnetic powder, the Fe content, calculated as Fe2O3, is preferably 40.0 mol % or more and 49.5 mol % or less (based on the total of the main components, the same applies below), and more preferably 45.0 mol % or more and 49.5 mol % or less.
[0101] In the calcined nonmagnetic powder, the Cu content, calculated as CuO, is preferably 6.0 mol % or more and 13.0 mol % or less (based on the total of the main components, the same applies below), and more preferably 7.0 mol % or more and 10.0 mol % or less.
[0102] In the calcined nonmagnetic powder, the Zn content, calculated as ZnO, is preferably 37.5 mol % or more and 54 mol % or less (based on the total of the main components, the same applies below), and more preferably 40.5 mol % or more and 48 mol % or less.
[0103] In addition, it can be safely assumed that the Fe content (converted into Fe2O3), Zn content (converted into ZnO), Cu content (converted into CuO), and Ni content (converted into NiO) in the above-mentioned calcined non-magnetic powder are substantially no different from the Fe content (converted into Fe2O3), Zn content (converted into ZnO), Cu content (converted into CuO), and Ni content (converted into NiO) in the above-mentioned sintered non-magnetic material after firing.
[0104] The above-mentioned calcined non-magnetic powder is used to create a green sheet in the same manner as the above-mentioned magnetic layer, which is then laminated in a predetermined location, and then, in the same manner as the above-mentioned magnetic layer, individual pieces are cut, sintered, and electrodes are formed, thereby producing the electronic component of embodiment 2.
[0105] (Embodiment 3)
[0106] A cross section of the electronic component of the third embodiment is shown in Fig. 9. The cross section of Fig. 9 corresponds to the cross section of Fig. 2 of the first embodiment.
[0107] As shown in FIG. 9, the electronic component of the third embodiment is similar to the electronic component 1 of the first embodiment, except that the lead-out portion is closer to one side surface.
[0108] Although one embodiment of the present invention has been described above, this embodiment can be modified in various ways.
[0109] Hereinafter, the electronic component of the present disclosure will be described with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0110] Working Example Preparation of magnetic materials A mixture was obtained by mixing 48.0 mol% Fe2O3, 21.0 mol% ZnO, 8.0 mol% CuO, and 23.0 mol% NiO. This mixture was wet mixed and pulverized, and then dried to remove moisture. The dried product was calcined at 800°C for 2 hours to obtain a magnetic material.
[0111] Conductive paste preparation The Ag powder was mixed with a given amount of solvent, resin, and dispersant in a planetary mixer, and then dispersed in a three-roll mill to prepare a conductive paste.
[0112] -Preparation of green sheets The obtained magnetic material was mixed in a ball mill with a predetermined amount of organic binder such as polyvinyl butyral, organic solvent such as ethanol or toluene, and plasticizer. Next, the material was formed into a sheet with a thickness of about 25 μm by a doctor blade method, and this was punched into a rectangular shape to produce a green sheet. In addition, the conductive paste was screen-printed on the green sheet to form a pattern of an internal conductor.
[0113] - Electronic component manufacturing The green sheets obtained above were laminated to a predetermined shape (see Figs. 2 to 4) and thermocompression-bonded to produce a laminate block. The laminate block obtained was cut with a dicer into individual pieces to obtain unfired bodies.
[0114] The unsintered body obtained above was sintered for 3 hours at a top temperature of 920°C to obtain an electronic component body. The obtained body was placed in a rotating barrel machine together with media, and rotated to form R's on the edges and corners of the body.
[0115] A conductive paste containing Ag and glass was applied to the end faces of the obtained element body, and baked at 820° C. to form a base electrode, thereby obtaining a sample of an electronic component.
[0116] Samples Nos. 1 to 28 were prepared by adjusting the internal conductor pattern and the number of layers so as to obtain the number and size of the internal conductors shown in the table below.
[0117] The dimensions of the electronic component fabricated were length (L) 3.2 mm, width (W) 2.5 mm, and height (T) 2.0 mm.
[0118] (evaluation) For each sample number, 30 samples obtained were visually evaluated for the presence or absence of cracks in the external electrodes. Sample numbers with no cracks were marked with an O, and sample numbers with at least one crack were marked with an X.
[0119] In addition, the following values were measured for each sample number. Width of insulator (w1) Width of the inner conductor exposed from the end face (w2) Width of the inner conductor lead (w3) -Width of the inner conductor line (w4) Height of insulator (h1) The distance (h2) between the first main surface of the uppermost internal conductor and the second main surface of the lowermost internal conductor on the first end face The distance (h3) between the first main surface of the uppermost internal conductor and the second main surface of the lowermost internal conductor in the line section -Thickness of the inner conductor line (t1) - Thickness of the insulation layer between the lines of the inner conductor (t2)
[0120] [Table 1]
[0121] [Table 2]
[0122] From the above results, it was confirmed that the samples in which the ratio of the height (h3) of the internal conductor at the line part of the laminate to the height (h1) of the insulator part is 0.25 or more and 0.55 or less, and the ratio of the width (w3) of the internal conductor lead part to the width (w1) of the insulator part is 0.40 or more and 1.0 or less do not have cracks in the external electrode. It was also confirmed that the samples in which the ratio of the protruding distance (p2) of the internal conductor to the width (w2) of the internal conductor exposed from the end face is 0.06 or less do not have cracks in the external electrode. It was confirmed that the ratio of the protruding distance (p1) of the most protruding internal conductor to the height (h2) of the internal conductor at the end face of the laminate is 0.06 or less does not have cracks in the external electrode. [Industrial Applicability]
[0123] The electronic components of the present disclosure may be used in a wide variety of applications, for example as impedance elements or inductors. [Explanation of symbols]
[0124] 1. Electronic components 3…Inner conductor 4…Line section 5…1st drawer part 6…Second drawer part 7…Insulation section 11...First end surface 12…Second end surface 13…Bottom surface 14…Top surface 15…1st side 16…Second side 17...First main surface of inner conductor 18...Second main surface of inner conductor 21...First external electrode 22…Second external electrode 31,32...Nonmagnetic layer
Claims
1. an insulating portion having a plurality of insulating layers laminated thereon; a plurality of band-shaped internal conductors embedded in the insulating portion; a first external electrode and a second external electrode provided opposite to an outer surface of the insulating body and electrically connected to the internal conductor; Equipped with the insulator portion has upper and lower surfaces opposed to each other, first and second end surfaces opposed to each other, and first and second side surfaces opposed to each other, the internal conductor has a first main surface which is a main surface on the upper surface side and a second main surface which is a main surface on the lower surface side, The internal conductor is laminated via the insulating layer, the insulating portion has a larger shrinkage rate during firing than the internal conductor; the internal conductor has a line portion and a first lead portion and a second lead portion located on both ends of the line portion, the first drawn-out portion and the second drawn-out portion are wider than the line portion in a top view, the first lead portion is exposed at the first end surface, and the second lead portion is exposed at the second end surface, The total cross-sectional area of the line portions of the multiple internal conductors is 0.1 mm 2 More than 0.5 mm 2 is as follows: a ratio of a distance between a first main surface of the line portion of the internal conductor closest to an upper surface of the insulator portion and a second main surface of the line portion of the internal conductor closest to a lower surface of the insulator portion to a height of the insulator portion is greater than or equal to 0.25 and less than or equal to 0.55; a ratio of a width of the lead portion of the internal conductor to a width of the insulating portion is 0.40 or more and 1.0 or less; Electronic components.
2. The electronic component according to claim 1 , wherein the number of said strip-shaped internal conductors is 2 or more and 5 or less.
3. 3. The electronic component according to claim 1, wherein the height of the insulating portion is not less than 1.8 mm and not more than 2.2 mm, and the width of the insulating portion is not less than 2.3 mm and not more than 2.7 mm.
4. 4. The electronic component according to claim 1, wherein the internal conductor has a protrusion protruding from the first end face and the second end face.
5. 5. The electronic component according to claim 1, wherein a protruding distance of the most protruding internal conductor at the first end face and the second end face is 0.05 mm or less, and a ratio of the protruding distance of the most protruding internal conductor to a distance between a first main surface of the internal conductor closest to an upper surface of the insulator portion and a second main surface of the internal conductor closest to a lower surface of the insulator portion is 0.06 or less.
6. 6. The electronic component according to claim 1, wherein a protruding distance of the internal conductor at the first end face and the second end face is 0.05 mm or less, and a ratio of the protruding distance of the internal conductor to a width of the internal conductor exposed at each end face is 0.06 or less.
7. 7. The electronic component according to claim 1, wherein the insulating layer located between the internal conductors has a thickness of 0.01 mm or more and 1.0 mm or less.
8. The insulating layer is Fe, Fe 2 O 3 In terms of the total amount, it is 40 mol % or more and 49.5 mol % or less. Zn is 2 mol % or more and 35 mol % or less, calculated as ZnO; Cu is 6 mol % or more and 13 mol % or less, calculated as CuO; Ni is 10 mol % or more and 45 mol % or less in terms of NiO The electronic component according to any one of claims 1 to 7, further comprising a first insulating layer comprising:
9. The insulating layer is Fe is 40 mol % or more and 49.5 mol % or less, calculated as Fe 2 O 3 ; Cu is 6 mol % or more and 13 mol % or less, calculated as CuO; Zn is 37.5 mol % or more and 54 mol % or less in terms of ZnO The electronic component according to any one of claims 1 to 8, further comprising a second insulating layer comprising:
Citation Information
Patent Citations
Laminated chip inductor
JP1998144526A
Composite magnetic material and electronic component using the same
JP2019210204A
Inductance element and electronic apparatus
JP2020088289A
Inductor
JP2021052180A
Inductor
JP2021100098A
